1997
DOI: 10.1007/s11665-997-0099-8
|View full text |Cite
|
Sign up to set email alerts
|

Tensile behavior and cyclic creep of continuous fiber-reinforced glass matrix composites at room and elevated temperatures

Abstract: In this study we investigated the stress-strain behavior at room and elevated temperatures and the tensile creep and cyclic creep response of a unidirectional SiC fiber-reinforced aluminosilicate glass matrix composite. The interfacial condition of the as-received material was measured by a push-out indentation technique. The stress-strain behavior was that expected for this kind of composite, i.e. "pseudoductile" behavior with extensive fiber "pull-out" at room temperature and brittle failure at intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…A similar increase in creep strain recovery ratio was observed during the 125 MPa creep-recovery test. Fairly high creep recovery ratios obtained for N720/A composite in this study are similar to the R cr values reported for the tensile cyclic creep-recovery of SiC/CAS [18] and SiC/AS composites [21], and for the flexural cyclic creep-recovery of SiC/BMAS composite [22].…”
Section: Cyclic Creep and Recoverysupporting
confidence: 89%
See 2 more Smart Citations
“…A similar increase in creep strain recovery ratio was observed during the 125 MPa creep-recovery test. Fairly high creep recovery ratios obtained for N720/A composite in this study are similar to the R cr values reported for the tensile cyclic creep-recovery of SiC/CAS [18] and SiC/AS composites [21], and for the flexural cyclic creep-recovery of SiC/BMAS composite [22].…”
Section: Cyclic Creep and Recoverysupporting
confidence: 89%
“…Holmes et al [17,20] investigated tensile creep and creep-recovery behavior of unidirectional SCS-6 SiC f /Si 3 N 4 composites in air at 1200 • C. Wu and Holmes [18,20] studied tensile creep and creep-recovery of 0 • and 0 • /90 • Nicalon SiC f /CAS-II composites at 1200 • in high-purity argon. Work in this field has also been performed by Boccaccini et al [21] for an aluminosilicate glass matrix composite reinforced with SiC (Nicalon) fibers and by Sun et al [22] for barium-magnesium-aluminosilicate matrix composite reinforced with SiC fibers. The experimental results reported in literature suggest that, when compared to sustained creep loading, elevated-temperature cyclic creep loading can decrease the overall creep strain accumulation in fiber-reinforced ceramics.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation